Preparation method of fly ash low-temperature detoxification building material fine aggregate

CN123003172APending Publication Date: 2026-10-30SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178519.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]当前行业内主流飞灰处置工艺普遍采用“先水洗脱盐、后成型烧结”的传统技术路线,存在诸多固有技术缺陷:原灰直接水洗易造成二噁英、炭粉、微量重金属等污染物外泄扩散,导致洗盐水浑浊、杂质含量高,后续水处理难度大、处置成本高;松散飞灰水洗后成型性能极差,成型颗粒结构松散、强度极低,水洗过程易崩解、入窑高温处理后易粉化,严重制约产品成型质量与良品率;飞灰中残留的氯盐、硫酸盐未彻底脱除,高温煅烧过程中易挥发并附着于窑体内壁,引发煅烧窑结圈、堵窑等故障,造成设备频繁停机运维,生产连续性大幅降低;传统高温煅烧解毒工艺能耗高、能效低,二噁英脱除不彻底,且重金属固化稳定性差,成品易出现重金属浸出超标问题,难以满足建材资源化利用的环保及性能标准

Benefits of technology

1、制粒原位封闭锁固污染物,彻底消除二次污染风险。本发明摒弃传统先水洗工艺,在制粒压实阶段将二噁英、未燃尽炭、有机杂质等污染物完整封闭包裹于颗粒内部,水洗全程无有机物、炭粉及有毒杂质溢出,洗盐水清澈透明、可循环回用,无二次污染物扩散,环保性能优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003172A_ABST
    Figure CN123003172A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of waste incineration waste harmless disposal, and particularly relates to a preparation method of fly ash low-temperature detoxification preparation of building material fine aggregate. The preparation method comprises the following steps: (1) modification, homogenization, granulation; (2) bottom wet heat steam penetration curing; (3) three-stage gradient salt washing; (4) drying; (5) hollow kiln low-temperature detoxification; (6) deep water washing after calcination; (7) heavy metal chelation stabilization. The present application constructs an integrated closed-loop process system of granulation in-situ pollution sealing, bottom wet heat penetration curing high-strength shaping, three-stage gradient clean immersion salt washing, low-temperature drying and stable type, hollow kiln low-temperature precise detoxification by biomass fuel heating, multi-stage water system cleaning after calcination, chelation and heavy resource stabilization, and biomass fuel residue recycling for modification agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of harmless disposal technology of waste from waste incineration, specifically relating to a method for preparing fine aggregate for building materials by low-temperature detoxification of fly ash. Background Technology

[0002] Municipal solid waste incineration fly ash is a highly hazardous solid waste generated during the incineration of municipal solid waste for power generation. It is rich in soluble chlorides, sulfates, dioxins and other persistent organic pollutants, as well as heavy metal ions. It is also mixed with unburned char and activated carbon adsorbing impurities. It is characterized by high toxicity, high risk of pollutant migration, difficulty in disposal, and prominent secondary pollution risks. It is a key hazardous waste category under control in the field of solid waste disposal.

[0003] The current mainstream fly ash treatment process in the industry generally adopts the traditional technical route of "washing and desalination first, followed by molding and sintering", which has many inherent technical defects: direct washing of raw fly ash can easily cause the leakage and diffusion of pollutants such as dioxins, carbon powder, and trace heavy metals, resulting in turbid wash water with high impurity content, making subsequent water treatment difficult and costly; loose fly ash has extremely poor molding performance after washing, with loose particle structure and very low strength, making it easy to disintegrate during the washing process and easy to pulverize after high-temperature treatment in the kiln, which seriously restricts the product molding quality and yield; residual chloride and sulfate in fly ash are not completely removed, which are easy to volatilize and adhere to the inner wall of the kiln during high-temperature calcination, causing kiln ring formation, kiln blockage and other failures, resulting in frequent equipment shutdowns and maintenance, and a significant reduction in production continuity; the traditional high-temperature calcination detoxification process has high energy consumption and low energy efficiency, incomplete dioxin removal, and poor stability of heavy metal solidification, making it easy for the finished product to have excessive heavy metal leaching, which is difficult to meet the environmental protection and performance standards for the resource utilization of building materials.

[0004] In addition, existing publicly available technologies and patented solutions generally lack core technology systems such as controllable molding with precise particle size of 1-4 mm, in-situ sealing and contamination locking, bottom wet heat penetration-type overall curing, and "hardening first, then washing". They cannot simultaneously solve multiple technical pain points in the fly ash disposal process, such as pollutant leakage, equipment blockage, high energy consumption, unstable product performance, and failure to meet environmental protection standards.

[0005] Furthermore, on the one hand, there are differences in understanding among those skilled in the art; on the other hand, the inventors studied a large number of documents and patents when making this invention, but due to space limitations, not all details and contents were listed in detail. However, this does not mean that the present invention does not possess the features of these prior art. On the contrary, the present invention already possesses all the features of the prior art, and the applicant reserves the right to add relevant prior art to the background art. Summary of the Invention

[0006] This invention belongs to the field of harmless disposal technology of waste from waste incineration, specifically relating to a method for preparing fine aggregate for building materials by low-temperature detoxification of fly ash.

[0007] To address the aforementioned technical problems, one objective of this invention is to provide a method for preparing building material fine aggregates through low-temperature detoxification of fly ash, comprising the following steps: (1) Modified homogenization granulation: The fly ash from waste incineration is mixed with the modifier in a dry, sealed manner according to the proportion to obtain a composite powder; water is added to the composite powder and stirred to wet it, and homogeneous solid particles are prepared by molding equipment; the mass of the modifier added is 30%~80% of the mass of the fly ash from waste incineration; the mass of water added is 11%~15% of the total mass of the composite powder; (2) Bottom hot steam penetration curing: Place the formed granules in a sealed silo, and introduce hot steam from the bottom of the silo to cure until the granule cylinder compressive strength is greater than 1.5 MPa; (3) Three-stage salt washing: The cured and hardened particles are washed and desalinated three times with reclaimed water in a fully submerged countercurrent circulation system; after the first salt washing, the salt content of particles with a diameter of 1~2 mm is not higher than 1.2%, the salt content of particles with a diameter of 3 mm is not higher than 1.8%, and the salt content of particles with a diameter of 4 mm is not higher than 2.2%; (4) Drying: Dry the washed salt granules until the moisture content of the granules is less than 5%; (5) Low-temperature detoxification in hollow kiln: The dried pellets are sent into a hollow kiln heated by biomass fuel and subjected to low-temperature heat treatment at 500~650℃; (6) Deep washing after calcination: The particles after low-temperature heat treatment are deeply washed with clean or medium water; so that the salt content of particles with a diameter of 1-2 mm is not higher than 0.5%, the salt content of particles with a diameter of 3 mm is not higher than 0.8%, and the salt content of particles with a diameter of 4 mm is not higher than 1.0%. (7) Heavy metal chelation stabilization: The organic composite heavy metal chelating agent is mixed with the particles in step (6) and then sieved to obtain fine aggregates of building materials with a diameter of 1~4 mm.

[0008] According to a preferred embodiment, in step (1), the modifier comprises, by mass percentage, 18.4% silica fume, 9.2% fly ash, and 64.4% mineral powder as the total cementing material, accounting for 92%; and 5% dolomite powder and 3% albite as the total auxiliary material, accounting for 8%. In step (1), the modifier comprises, by mass percentage, 20% silica fume, 10% fly ash, 62% mineral powder, 5% dolomite powder, and 3% albite.

[0009] According to a preferred embodiment, in step (1), the particle size of the shaped particles is 1~4 mm. Preferably, the particle size of the shaped particles is 1 mm. The particle size of the shaped particles is 2 mm. The particle size of the shaped particles is 3 mm. The particle size of the shaped particles is 4 mm.

[0010] According to a preferred embodiment, in step (2), the sealed silo is a funnel-shaped bottom silo.

[0011] According to a preferred embodiment, in step (2), a maintenance method of bottom-up penetrating humidification and synchronous gradient heating is adopted.

[0012] According to a preferred embodiment, in step (3), after three water washings and drying treatment, the salt content of the material is not higher than 0.91%.

[0013] According to a preferred embodiment, in step (4), the drying temperature is 500~650℃. Preferably, the drying temperature is 500℃. Preferably, the drying temperature is 580℃. Preferably, the drying temperature is 650℃.

[0014] According to a preferred embodiment, in step (7), the organic composite heavy metal chelating agent comprises a piperazine dithiocarbamate sodium chelating agent and a hexathioguanidine chelating agent.

[0015] One of the objectives of this invention is to provide a method for preparing building material fine aggregate by low-temperature detoxification of fly ash, wherein the building material fine aggregate is prepared based on the above-mentioned preparation method.

[0016] One of the objectives of this invention is to provide the use of the above-mentioned fly ash low-temperature detoxification method for preparing fine aggregates for building materials.

[0017] The beneficial effects of this technical solution are: 1. In-situ sealing and consolidation of pollutants during granulation completely eliminates the risk of secondary pollution. This invention abandons the traditional pre-washing process and completely seals and encapsulates pollutants such as dioxins, unburned carbon, and organic impurities inside the granules during the granulation and compaction stage. No organic matter, carbon powder, or toxic impurities are spilled out during the entire washing process. The washing brine is clear, transparent, and recyclable, with no secondary pollutant diffusion, resulting in excellent environmental performance.

[0018] 2. Bottom-level wet-heat steam penetration curing significantly improves the stability of particle structure. Referring to Comparative Example 1, the bottom-up, full-area penetration wet-heat curing mechanism ensures uniform and sufficient particle hydration reaction. After curing, the cylinder pressure is consistently greater than 1.5 MPa, exhibiting excellent resistance to water washing, disintegration, and pulverization. This completely solves the problems of loosening, breakage, and pulverization caused by traditional particle washing, ensuring the continuous and stable operation of subsequent desalination and calcination processes.

[0019] 3. Multi-stage, precise desalination eliminates equipment blockage at its source. A dual desalination system is employed, combining a three-stage pre-treatment immersion washing with 1-3 deep water washes after calcination. This achieves differentiated and precise desalination for particles of different sizes, resulting in a highly controllable and significantly reduced salt content in the finished product. This completely avoids the ring formation and kiln blockage problems caused by the high-temperature volatilization of chlorides and sulfates, effectively extending equipment maintenance cycles, improving production continuity, and reducing maintenance costs.

[0020] 4. Low-temperature detoxification of biomass fuel results in low energy consumption, low cost, and thorough removal of pollutants. The use of a 500-650℃ low-temperature calcination process for biomass fuel replaces the traditional high-temperature sintering process, significantly reducing production energy consumption and equipment heat loss. This allows dioxins encapsulated within the pellets to be fully heated and released, resulting in complete detoxification and eliminating any residual pollution risks.

[0021] 5. Precise and controllable particle size gradient, adaptable to building material fine aggregate application standards. It can stably prepare particles with a continuous gradient size of 1~4 mm, with uniform product gradation and good performance consistency, fully meeting the technical requirements for particle size, strength, and stability of building fine aggregates, and has high resource-based added value.

[0022] 6. Long-term curing of heavy metals ensures the finished product meets environmental and safety standards. Through uniform impregnation treatment with an organic composite heavy metal chelating agent, residual heavy metal ions inside the particles are transformed into stable, insoluble complexes, effectively inhibiting heavy metal leaching. The finished product fully complies with the environmental leaching standards for building materials, ensuring safe and reliable engineering applications.

[0023] 7. Highly innovative process with strong adaptability for large-scale promotion. This invention pioneers a new process logic of "first forming to lock in dirt, then hardening and washing, and low-temperature detoxification for stability," avoiding the homogeneity defects of existing patented technologies. The process route is simple and controllable, with strong operational stability, and can be adapted to large-scale industrial continuous production, with broad prospects for industrialization and promotion. Attached Figure Description

[0024] Figure 1 This is a process flow diagram related to the present invention; Figure 2 It is a fine aggregate for building materials. Detailed Implementation

[0025] In the description of this invention, terminology is used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly defined.

[0026] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents or instruments used, unless otherwise specified by the manufacturer, are all commercially available reagents and materials; the conditions not specified in the examples are all carried out according to conventional conditions or conditions recommended by the manufacturer. At the same time, the present invention does not limit the source of the raw materials used. Unless otherwise specified, the raw materials used in the present invention are all commercially available products in this technical field.

[0027] The modifier is a powdered modifying material used to mix with waste incineration fly ash to improve the fly ash's molding performance, hydration hardening performance, and particle structure stability. Its components include a cementing material that undergoes a hydration reaction with the fly ash. In this application, the modifier, by mass percentage, is as follows: 92% cementing material (18.4% silica fume, 9.2% fly ash, and 64.4% mineral powder), and 8% colorant + co-solvent, i.e., the total proportion of auxiliary materials (5% dolomite powder and 3% albite).

[0028] Bottom reverse humid heat steam penetration curing involves placing the formed granules in a sealed silo and introducing humid heat steam from the bottom of the silo in reverse, allowing the steam to penetrate the entire granule layer from bottom to top, simultaneously achieving granule humidification, heating, and hydration hardening curing.

[0029] The tiered countercurrent circulation salt washing process employs a three-stage water washing procedure. The washing solution at each stage is recycled in the opposite direction to the particle flow, and the salt washing process achieves graded desalination by relying on the difference in the permeation rate of particles of different sizes.

[0030] Hollow kilns are heat treatment furnaces that use biomass fuel for heating and have a hollow cavity structure, which can effectively isolate flue gas from the pyrolysis gases of materials.

[0031] In-situ sealing and pollution locking refers to the technical effect of completely encapsulating and sealing the original pollutants such as dioxins, activated carbon, and unburned organic matter in fly ash inside the particle matrix during the granulation and compaction process, preventing them from migrating and diffusing outward.

[0032] The organic composite heavy metal chelating agent comprises dithiocarbamate derivative chelating agents and hydroxyaminocarboxylic acid chelating agents. Specifically, the organic composite heavy metal chelating agent used in the following examples is a mixture of commercially available sodium piperazine dithiocarbamate and hexathioguanidine in a mass ratio of 2:1. The yield of the organic composite heavy metal chelating agent is 2% to 5% of the fly ash mass.

[0033] Example 1 (Small particle size, low doping ratio) like Figure 1 As shown, municipal solid waste incineration fly ash was selected as raw material, and 30% of the fly ash mass of modifier was added. The mixture was then dry-homogenized and mixed with the fly ash in a closed environment to obtain a homogeneous composite powder. 11% of the total mass of water was added to the composite powder, and after stirring and wetting, 1 mm homogeneous solid particles were prepared.

[0034] Freshly formed granules are conveyed to a funnel-shaped sealed silo, where hot, moist steam is introduced from the bottom at 60°C and cured from bottom to top. The curing conditions are stabilized until the granule cylinder compressive strength reaches 1.62 MPa.

[0035] The hardened pellets were subjected to a three-stage countercurrent immersion salt washing process using reclaimed water in three desalination tanks connected in series. After the first washing, the salt content of the pellets was 1.12%. They were then sent to a low-temperature drying device to control the moisture content of the finished product to 4.22%. Next, they were transferred to a hollow kiln heated by biomass fuel, where the material was kept at a constant temperature of 500℃ for 30 minutes to thoroughly remove dioxins from the pellets. After calcination, a deep washing with reclaimed water was performed, reducing the salt content of the pellets to 0.41%.

[0036] Finally, the particles were uniformly impregnated and stabilized with an organic composite heavy metal chelating agent at 2% of the fly ash mass to solidify residual heavy metals. After homogenization and sieving, 1 mm fine aggregate meeting building material standards was obtained. Biomass fuel residue was used to formulate fly ash modifiers.

[0037] Tests showed that the dioxin content of the finished product was below the detection limit, and the leaching concentration of heavy metals fully complied with the GB / T 2542-2012 building materials testing standard. The water quality was clear throughout the washing process, with no impurities or pollutants overflowing. The hollow kiln operated stably without any ring formation or kiln blockage.

[0038] Example 2 (Conventional Particle Size Ratio) Using fly ash from the same batch as in Example 1 as raw material, 50% of the fly ash mass of modifier was added for dry, sealed homogenization. 13% of the total powder mass of water was added, and the mixture was stirred until homogeneous, then 3 mm homogeneous particles were formed. After curing with hot steam penetrating the bottom of a sealed silo, the compressive strength of the particles reached 1.59 MPa. After three-stage immersion washing with recycled water, the salt content of the particles after the first wash was 1.73%; after low-temperature drying, the moisture content was controlled at 3.78%. The dried particles were sent to a hollow kiln, where they were kept at 580℃ for 20 minutes to complete low-temperature detoxification. Two deep washings with clean water were then performed, resulting in a final product with a salt content of 0.73%. After impregnation and stabilization treatment with 3% of the fly ash mass of organic composite chelating agent, qualified 3 mm building material fine aggregate was obtained.

[0039] Testing revealed that the finished product has a dense structure, stable mechanical properties, and a high degree of harmlessness, with no risk of heavy metal leaching, complete removal of dioxins, no pollutant leakage throughout the production process, and stable equipment operation. All indicators meet the standards for the resource utilization of building materials. Biomass fuel residue is recycled to prepare fly ash modifiers.

[0040] Example 3 (Large Particle Size, High Dosage Ratio) Using fly ash from the same batch of waste incineration as raw material, 80% modifier by weight of fly ash was added and thoroughly homogenized in a sealed environment. 15% water by weight of the total powder was added, and after stirring and wetting, 4 mm homogeneous particles were prepared. After bottom-mounted reverse hot steam penetration curing, the compressive strength of the particles reached 2.65 MPa. After three-stage cascade salt washing, the salt content of the particles after the first wash was 2.18%, and the moisture content after low-temperature drying was controlled at 4.46%. The dried particles were sent to a hollow kiln, where they were kept at 650℃ for 15 minutes to complete low-temperature detoxification. Three deep washings with medium water were then carried out, resulting in a final salt content of 0.96%. After 5% heavy metal chelation stabilization treatment by fly ash weight and homogenization screening, qualified 4 mm building material fine aggregate was obtained. Figure 2 As shown.

[0041] Testing revealed that the high modifier dosage in this embodiment resulted in excellent particle formability, good water resistance and anti-disintegration properties, thorough low-temperature detoxification, and no kiln ring formation or blockage issues during the production process. The finished product's gradation, strength, and environmental protection indicators fully meet the requirements for the resource utilization of building materials.

[0042] Comparative Example 1 (Steam Curing) Using fly ash from the same batch as in Example 1 as raw material, 50% modifier by weight of fly ash was added and dry-processed in a sealed environment for homogenization. 13% water by weight of the total powder was added, and the mixture was stirred evenly before molding into 1mm homogeneous particles. After natural curing at 20℃, the particle cylinder compressive strength was 0.1 MPa after 1 day (completely disintegrated after soaking in water), 0.3 MPa after 7 days (most particles disintegrated after water soaking and agitation for desalination), and 1.1 MPa after 20 days (suitable for desalination). After three-stage immersion washing with recycled water, the salt content of the particles after the first wash was 1.73%; the moisture content after low-temperature drying was controlled at 3.78%. The dried particles were sent to a hollow kiln, where they were kept at 580℃ for 20 minutes to complete low-temperature detoxification. Two deep water washes were then performed, resulting in a final product with a salt content of 0.73%. After impregnation and stabilization treatment with 5% organic composite chelating agent by weight of fly ash, qualified 3mm building material fine aggregate was obtained.

[0043] It can be seen that there is a significant difference in the enhancement cycle between high-temperature curing and natural curing, and steam curing is the preferred option for industrial production.

[0044] Comparative Example 2 (Traditional Process Control Group) The industry's traditional process of "washing first, then shaping, and high-temperature calcination" is used to process fly ash from the same batch of waste incineration.

[0045] The raw fly ash is directly washed with water, and the washing brine is turbid and black, carrying a large amount of carbon powder, organic pollutants and trace heavy metal impurities, and the problem of pollutant leakage and diffusion is prominent. Loose fly ash is difficult to form after washing, and the formed particles have a loose structure and no effective strength. They completely disintegrate during the washing process and cannot achieve stable shaping.

[0046] After the material is calcined at 850℃, a large amount of residual chloride and sulfate in the fly ash volatilizes and adheres to the kiln wall, causing severe ring blockage in the hollow kiln. This necessitates frequent equipment shutdowns for maintenance, resulting in extremely poor production continuity. Traditional processes produce finished products with problems such as dioxin residues, excessive heavy metal leaching, low particle strength, and large-scale pulverization after calcination. These issues fail to meet the standards for fine aggregates used in building materials, and the process stability, environmental friendliness, and product performance are significantly inferior to the process of this invention.

[0047] To directly verify the technological advancement, product stability, and environmental advantages of the present invention, the finished products of each embodiment and the comparative products of the traditional process were uniformly tested according to current national standards. The testing standards included "Construction Sand" (GB / T2542-2012), "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB 5085.3-2007), and relevant industry standards for the pollution control of fly ash from municipal solid waste incineration. The test results are shown in Table 1.

[0048] Table 1

[0049] This invention constructs an integrated closed-loop process system that includes in-situ closed-loop granulation to lock in contaminants, bottom wet heat penetration curing for high-strength shaping, three-stage tiered cleaning and immersion salt washing, low-temperature drying and stabilization, low-temperature precise detoxification in a hollow kiln heated by biomass fuel, multi-stage water system cleaning after calcination, chelation stabilization and resource recovery, and recycling of biomass fuel residues for modifiers.

[0050] Meanwhile, the cascade washing process is divided into two parts: one before high-temperature treatment and one after high-temperature treatment. The cascade washing before high-temperature treatment can remove most of the soluble chloride salts in the particles. The cascade washing after high-temperature treatment causes the water-containing substances in the particles to lose their water of crystallization, thereby increasing the pore size within the particles and achieving deep removal of residual chloride salts, further effectively reducing the chloride salt content in the particles.

[0051] In addition, the low-temperature detoxification of the hollow kiln heated by biomass fuel can effectively isolate the flue gas and the gas after dioxin pyrolysis, reducing the cost of subsequent waste gas treatment. On the other hand, the use of biomass fuel to provide heat can significantly reduce the cost of fly ash treatment, realizing a new way to treat fly ash at low cost.

[0052] It should be noted that the specific embodiments described above are exemplary, and those skilled in the art can devise various solutions inspired by the disclosure of this invention, all of which fall within the scope of this invention and its protection. Those skilled in the art should understand that this specification is illustrative and not intended to limit the scope of the claims. The scope of protection of this invention is defined by the claims and their equivalents.

Claims

1. A method for preparing building material fine aggregate through low-temperature detoxification of fly ash, characterized in that, Includes the following steps: (1) Modified homogenization and granulation: The fly ash from waste incineration is mixed with the modifier in a dry, sealed manner according to a certain ratio to obtain a composite powder; water is added to the composite powder and stirred to wet it, and homogeneous solid particles are prepared by molding equipment; the mass of the modifier added is 30% to 80% of the mass of the fly ash from waste incineration; the mass of the water added is 11% to 15% of the total mass of the composite powder; (2) Bottom-level hot steam penetration curing: Place the formed granules in a sealed silo and introduce hot steam from the bottom of the silo to cure until the granule cylinder compressive strength is greater than 1.5 MPa; (3) Three-stage salt washing: The cured and hardened particles are washed and desalinated three times with reclaimed water in a fully submerged countercurrent circulation system; after the first salt washing, the salt content of particles with a diameter of 1~2 mm is not higher than 1.2%, the salt content of particles with a diameter of 3 mm is not higher than 1.8%, and the salt content of particles with a diameter of 4 mm is not higher than 2.2%; (4) Drying: Dry the washed salt granules until the moisture content of the granules is less than 5%; (5) Low-temperature detoxification in hollow kiln: The dried pellets are sent into a hollow kiln heated by biomass fuel and subjected to low-temperature heat treatment at 500~650℃; (6) Deep washing after calcination: The particles after low-temperature heat treatment are deeply washed with clean or medium water; so that the salt content of particles with a diameter of 1-2 mm is not higher than 0.5%, the salt content of particles with a diameter of 3 mm is not higher than 0.8%, and the salt content of particles with a diameter of 4 mm is not higher than 1.0%. (7) Heavy metal chelation stabilization: The organic composite heavy metal chelating agent is mixed with the particles in step (6) and then sieved to obtain fine aggregates of building materials with a diameter of 1~4 mm.

2. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (1), the modifier contains 20% silica fume, 10% fly ash, 62% mineral powder, 5% dolomite powder and 3% sodium feldspar by mass percentage.

3. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (1), the particle size of the shaped particles is 1~4 mm.

4. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (2), the sealed silo is a funnel-shaped bottom silo.

5. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (2), a maintenance method of bottom-up penetrating humidification and synchronous gradient heating is adopted.

6. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (3), the material is dried after three water washes, and the salt content is no higher than 0.91%.

7. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (4), the drying temperature is 500~650℃.

8. The method for preparing building material fine aggregate by low-temperature detoxification of fly ash according to claim 1, characterized in that, In step (7), the organic composite heavy metal chelating agent includes dithiocarbamate derivative chelating agents and hydroxyaminocarboxylic acid chelating agents.

9. A method for preparing building material fine aggregate through low-temperature detoxification of fly ash, characterized in that, The fine aggregate for building materials is prepared based on the preparation method described in any one of claims 1-8.

10. The use of the fly ash low-temperature detoxification preparation of fine aggregate for building materials as described in claim 9 in building materials.